Enzyme-assisted Cyclization of Chalcones to Flavanones - Alonso, Mariana Macías; Boluda, Carlos José; Barajas, Gabriela Díaz; Sánchez, Nallely C.; Córdova-Guerrero, Iván; Marrero, Joaquín González (Letters in Organic Chemistry, 2020)
Enzyme catalyzed synthesis is an eco-friendly technique in organic synthesis, having several benefits over conventional methods. In the present work, we describe a simple process of laccase and chloroperoxidase assisted cyclization of chalcones, leading to the formation of flavanones. The reaction proceeds in a mixture of phosphate buffer and ethanol, under oxygen atmosphere at room temperature, yielding the corresponding flavanone in good to moderate yield. The relative configuration of the products at C2 is tentatively assigned as S*-flavanone based on the coupling constants with the methylenic protons H3α,β. In comparison to the chemical methods, we describe a process which can be achieved efficiently under mild conditions using oxygen as oxidant.
Keywords: flavonoids